Thermal sintering: a novel technique in the design of gastroretentive floating tablets of propranolol HCl and its evaluation - Srikanth Meka, Venkata; Sunil Songa, Ambedkar; Rao Nali, Sreenivasa; Ram Battu, Janaki; Kukati, Latha; Murthy Kolapalli, Venkata Ramana (Investigación Clínica, 2012)
Â  The aim of the present investigation was to formulate thermally sintered floating tablets of propranolol HCl, and to study the effect of sintering conditions on drug release, as well as their in vitro buoyancy properties. A hydrophilic polymer, polyethylene oxide, was selected as a sintered polymer to retard the drug release. The formulations were prepared by a direct compression method and were evaluated by in vitro dissolution studies. The results showed that sintering temperature and time of exposure greatly influenced the buoyancy, as well as the dissolution properties. As the sintering temperature and time of exposure increased, floating lag time was found to be decreased, total floating time was increased and drug release was retarded. An optimized sintered formulation (sintering temperature 50°C and time of exposure 4 h) was selected, based on their drug retarding properties. The optimized formulation was characterized with FTIR and DSC studies and no interaction was found between the drug and the polymer used.